2021
DOI: 10.18231/j.ijcap.2020.078
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical variations of papillary muscles in human cadaveric hearts of Chhattisgarh, India

Abstract: Background: In both ventricles of the heart papillary muscles play important role for proper cardiac valvular function of heart. The present study was done to analyse the papillary muscles of heart with respect to the variations in their number, length, shape, position and pattern in both ventricles. Materials and Methods: Forty well preserved cadaveric human hearts were used for the study. The variations in the papillary muscles of both right and left ventricles were categorized, documented and photographed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…The mean length of the papillary muscle (both anterior and posterior) in the left ventricle was longer in numerous heart specimens when compared to other heart specimens of the right ventricle. The comparison of the latest research with Manisha's study is generally similar because the current study demonstrated a greater length of the three papillary muscles of the right ventricle (Sinha et al, 2021). Kavitha et al (2018) and Marius et al (2018) measured the anterior 14.89 (4.19) mm, posterior 14.86 (4.05) mm, and septal muscle 10.27 (3.28) mm of the right ventricle.…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…The mean length of the papillary muscle (both anterior and posterior) in the left ventricle was longer in numerous heart specimens when compared to other heart specimens of the right ventricle. The comparison of the latest research with Manisha's study is generally similar because the current study demonstrated a greater length of the three papillary muscles of the right ventricle (Sinha et al, 2021). Kavitha et al (2018) and Marius et al (2018) measured the anterior 14.89 (4.19) mm, posterior 14.86 (4.05) mm, and septal muscle 10.27 (3.28) mm of the right ventricle.…”
Section: Resultssupporting
confidence: 79%
“…3). Sinha et al (2021), discovered that the thickness of the anterior, posterior, and septal papillary of the right ventricle was 1.27±0.45 cm, 1.36±0.52 cm, and 0.92±0.54 cm respectively. The mean length of the papillary muscle (both anterior and posterior) in the left ventricle was longer in numerous heart specimens when compared to other heart specimens of the right ventricle.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The gradual delamination of the ventricular wall is responsible for the embryological development of heart muscles. Its incomplete delamination might lead to distortion in the external appearance of papillary muscles [ 14 ]. The interior of the heart is specially adapted to maintain the rapid conduction of cardiac impulses [ 15 ].…”
Section: Introductionmentioning
confidence: 99%